Nursing diagnosis of patients with colorectal neoplasia undergoing chemotherapy treatment - a qualitative research - Priscila Oliveira Silva; Maria Isabel Pinto Coelho Gorini (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="61" S